2016
DOI: 10.1016/j.jsr.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of teen driving: Restrictions, worry and influence

Abstract: Introduction Parents play a critical role in preventing crashes among teens. Research of parental perceptions and concerns regarding teen driving safety is limited. We examined results from the 2013 Summer ConsumerStyles survey that queried parents about restrictions placed on their teen drivers, their perceived level of “worry” about their teen driver’s safety, and influence of parental restrictions regarding their teen’s driving. Methods We produced frequency distributions for the number of restrictions im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Parents worry more about their new drivers when they are learning to drive and are under supervision compared to when they are newly licensed drivers and are more likely to crash (Jewett, Shults & Bhat, 2016). Another benefit of the introduction of a formal TPP framework is that it may clearly alert parents to the dangers present for their child when they first start to drive by themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents worry more about their new drivers when they are learning to drive and are under supervision compared to when they are newly licensed drivers and are more likely to crash (Jewett, Shults & Bhat, 2016). Another benefit of the introduction of a formal TPP framework is that it may clearly alert parents to the dangers present for their child when they first start to drive by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…There is an implicit assumption that they will be involved in the GDL process (Glendon, 2013;Mayhew, 2003) and young drivers tend to operate a vehicle in a similar way to their parents (Schmidt, Morrongiello & Colwell, 2014;Strukcinsiene et al, 2014). Parents themselves believe that parental rules have a significant impact on the risk that a young driver will be involved in crash (Jewett, Shults & Bhat, 2016). Parental involvement appears to be influenced by the parenting style and practices that they used prior to the licensing processes (Laird, 2014).…”
Section: Parental Influencementioning
confidence: 99%
“…Parents do intend on placing limits on their young drivers unsupervised driving (Hartos et al, 2004) and parents appear to be able to do this more effectively when a GDL system is in place (Hartos et al, 2005). One study suggested that 80% of parents have rules or restrictions for their learner or intermediate driver (Jewett et al, 2016) with a New Zealand study finding that when parents had low knowledge of GDL conditions their young driver was less likely to comply (Brookland et al, 2014). A review of parent involved teen driving interventions suggests that those based on theory and actively involving parents are more likely to be successful (Curry et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%